HUBUNGAN KINERJA OTAK DENGAN SPIRITUALITAS MANUSIA DIUKUR DENGAN MENGGUNAKAN INDONESIA SPIRITUAL HEALTH ASSESSMENT PADA PEGAWAI PEMDA KABUPATEN HALTENG PROVINSI MALUKU UTARA - ., Juniarsih; Pasiak, Taufiq F.; Wangko, Sunny (eBiomedik, 2015)
Abstract: Brain is the most complex part of human body. It regulates, monitors, and controls our actions and behaviors. By using SPECT, Amen observed the brain activity associated with soul and divided brain into 5 main systems: the prefrontal cortex, limbic system, basal ganglia, cingulatus gyrus (cingulate), and the temporal lobe. Spirituality is an empirical experience related to the presence of God in one's life with its manifestations in interpersonal and intrapersonal relationships. Spirituality has four dimensions, which are the meaning of life, spiritual experiences, positive emotions, and rituals. The spiritual measuring device used in Indonesia is Indonesia Spiritual Health Assessment (ISHA). This study aimed to determine the correlation between the human brain performance and spirituality measured with ISHA among employees (echelon II and III) in Halmahera Tengah, North Maluku province. This was a descriptive correlative study with a survey method. The Spearmanâ€™s rank test showed an inversely correlation (-0.005) with a sig. 0.968 > Î± = 0.05, which means that there is no correlation between the performance of human brain and spirituality, especially positive emotions and the limbic system. Conclusion: There was no correlation between the performance of the human brain and spirituality especially positive emotions and the limbic system.Keywords: ISHA, brain, spirituality.Absrak: Otak merupakan bagian tubuh manusia yang sangat kompleks serta mengatur, mengawasi, dan mengendalikan tindakan dan perilaku tubuh. Dengan menggunakan SPECT, Amen mengamati aktivitas otak yang berhubungan dengan jiwa dan membagi otak dalam 5 sistem utama yaitu korteks prefrontalis, sistem limbik, ganglia basalis, Gyrus cingulatus (singulat), dan lobus temporalis. Spiritualitas adalah suatu pengalaman empirik berkaitan dengan kehadiran Tuhan dalam kehidupan seseorang dengan manifestasinya dalam hubungan interpersonal dan intrapersonal. Spiritualitas mempunyai 4 dimensi yaitu makna hidup, pengalaman spiritual, emosi positif, dan ritual. Di Indonesia alat ukur spiritual yang digunakan yaitu Indonesia Spiritual Health Assessment (ISHA). Penelitian ini bertujuan untuk mengetahui hubungan kinerja otak dengan spiritualitas manusia yang diukur menggunakan ISHA pada pegawai (pejabat essalon II dan III) Pemda Kabupaten Halmahera Tengah Provinsi Maluku Utara. Penelitian ini menggunakan metode deskriptif korelatif dan survei. Hasil uji korelasi Spearman menunjukkan korelasi terbalik (-0,005) dengan sig 0,968 > ðœ¶=0,05. Simpulan: Tidak terdapat hubungan antara kinerja otak dan spiritualitas khususnya emosi positif dan sistem limbik.Kata kunci: ISHA, otak, spiritualitas